Application of Analytical Hierarchy Process (AHP) in Determining Maritime Defense Strategy as a Follow-Up to Conflict in Natuna Sea - Yudi Sutrasna,Ahmad SugionoHendra Wulan1Januar Arief Martharaharja (International Journal of Advanced Science and Technology, 2020)
Conflicts between countries located side by side due to differences of opinion regarding national borders is a common thing. In responding to border conflicts that may arise in the future, the Indonesian government must place the national security factor as the main consideration in making strategic decisions to create and maintain national security in the long term. There are at least five national security sub-systems, namely State Security; Territory Security; Human Security; Infrastructure Security; and Public Security. The five national security sub-systems can be used as criteria in determining the most appropriate long-term national security strategy to be applied in accordance with the situation at hand. The alternative strategies that can be chosen include Updating Military Resources (Alutsista); Application of Integrated Security Surveillance Technology; Massive State Defending Education to the Community; Mobilization of Various Community Components; Establishing Defense Cooperation with Neighboring Countries; and strict law enforcement without discrimination. To find out the most appropriate alternative strategies to be selected and implemented in order to create and maintain national security in the long run as a follow up to the Natuna Sea conflict with China will be carried out using AHP analysis techniques. The results of the study stated that the best strategy that could be chosen and applied in the context of following up the Natuna sea conflict with China isa strict law enforcement strategy.